2005
DOI: 10.1238/physica.regular.072a00389
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Model for the Ionization Cross Sections of H- and He-Like Ions

Abstract: A simple modification of the empirical model of Hombourger (HEMP) [1998 J. Phys. B 31 3693] is proposed with ionic and relativistic corrections in it. The modified HEMP (MHEMP) model has been applied to 11 H- and He-like ionic targets with a wide range of atomic numbers Z = 5–92 to calculate the electron impact single ionization (EISI) cross sections. MHEMP with a single set of parameter values is found to describe excellently the experimental EISI cross sections of B4+, C4+, N6+, O7+, Ne8+, Mo41+, Dy65+, Au78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…We have observed that the Mott and Born parts of σ QIBED need different relativistic correction factors for description of the experimental data. While R B is alike the factor used in 17–19, the former factor R M resembles the one employed earlier in 26.…”
Section: Outline Of the Modelsmentioning
confidence: 99%
“…We have observed that the Mott and Born parts of σ QIBED need different relativistic correction factors for description of the experimental data. While R B is alike the factor used in 17–19, the former factor R M resembles the one employed earlier in 26.…”
Section: Outline Of the Modelsmentioning
confidence: 99%